Analisis Kemandirian Peserta Didik Kelas 1B dalam Penerapan Pembelajaran Projek Penguatan Profil Pelajar Pancasila (P5) di SD Negeri Tugu Jebres Surakarta Tahun Pelajaran 2023/2024 - Vicky Firnanda; Anita Trisiana; Oka Irmade (Departement of Mathematics Education, 2024)
The aim of this research is 1) to determine the independence of class 1B students in implementing P5 learning. 2) knowing the form of independence of class 1B students in implementing P5 learning. 3) know and describe the factors that influence the independence of class 1B students in implementing P5 learning. 4) find out what efforts are made by the school to overcome problems that arise in the implementation of P5 learning related to the independence of class 1B students. This research was carried out at Tugu Jebres Elementary School, Surakarta. This form of research uses descriptive qualitative research methods. This research strategy uses a qualitative descriptive design with a case study approach. The subjects of this research included class 1B teachers, class 1B students and parents of class 1B students. The object of this research is independence in implementing P5 to increase the independent character value of class 1B students at SD Negeri Tugu Jebres Surakarta. The data collection techniques used were observation, interviews and documentation. The results of the research can be concluded that: 1) the independence of class 1B students in implementing P5 at SD Negeri Tugu Jebres Surakarta consists of 6 indicators. The independence of class 1B students in implementing P5 is categorized as 80% of students being independent. 2) the form of independence of class 1B students in implementing P5 learning includes students being able to learn on their own. 3) factors that influence the independence of class 1B students in implementing P5 learning are influenced by internal factors and external factors. 4) the efforts made by the school to overcome problems that arise in the implementation of P5 learning are that teachers and the school will always encourage, motivate and provide opportunities for students so that they can learn and be independent.